PENGARUH SANKSI PERPAJAKAN, PENGETAHUAN PAJAK DAN PERSEPSI WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK (Studi Kasus Wajib Pajak Badan KPP Semarang Tengah II) - Hari Candra, 08.05.52.0161; Wahyudi, Djoko (Students Journal of Accounting and Banking, 2013)
This study aims to examine and analyze the effect of tax penalties, tax knowledge, perception of the tax man and the criteria required to adhere to compliance of corporate taxpayers. The population in this study is the Taxpayer who are in KPP Pratama Semarang Tengah II. Sampling method used was a non-probability sampling technique, which is convenience sampling. Samples obtained as many as 103 respondents. The data analysis technique used is multiple linear regression analysis. Based on the results of the tests performed can be seen that the tax penalties, tax knowledge, perception of the tax man and the criteria required to comply with a positive and significant impact on taxpayer compliance body, either partially or simultaneouslyKeywords: tax penalties, tax knowledge, perception of the tax man, and compliance criteria required to comply with corporate taxpayers